A mass spectrometry-based unique fragment approach for the identification of microcystins. Issue 4 (19th December 2014) - Benke, P. I.; Vinay Kumar, M. C. S.; Pan, D.; Swarup, S.
Abstract : Both qualitative and quantitative methods for the analysis of microcystin variants have been established. Abstract : Both qualitative and quantitative methods for the analysis of microcystin variants have been established. The qualitative method involves a unique fragment approach, specific for each variant in identifying microcystins, while the quantitative method involves the quantification of microcystins in cellular matrices of cyanobacteria and reservoir water samples. For the identification of fragments associated with their respective microcystin (MC) variants, theoretically obtained fragments of microcystins were compared with tandem mass spectrometric (MS/MS) fragments obtained from an ESI-Orbitrap mass spectrometer. Here, we present the first report of MC variants produced by the model algal strain M. aeruginosa NIES-843. A robust comparative study between the unique fragments and the conventional product ions for quantitative measurements of microcystin has also been carried out. The method with high robustness was further validated by determining the MC level changes in the intracellular matrices of M. aeruginosa samples, grown under high and low nitrogen conditions, and by testing the amount of MC in environmental water samples.